2022
DOI: 10.1002/lary.30329
|View full text |Cite
|
Sign up to set email alerts
|

Economic Viability of Penicillin Allergy Testing to Avoid Improper Clindamycin Surgical Prophylaxis

Abstract: Objective Patients mislabeled with a penicillin allergy are often unnecessarily given prophylactic clindamycin. Thus, otolaryngologists may cause harm due to clindamycin's associated risk of Clostridioides difficile infections (CDI) and surgical site infections (SSI). The objective of this study was to determine the economic feasibility of penicillin allergy testing in preventing unnecessary clindamycin use among patients with an unconfirmed penicillin allergy prior to otolaryngologic surgery. Methods A break‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…Preoperative allergy assessment and/or de-labeling also involve a significant financial and time outlay. Liu et al performed an evaluation of the cost of implementing PST relative to the benefit, and they found that the degree to which performing PST made financial sense was dependent on the rates of C. difficile infection and SSIs at an institution [59]. PST supplies and training are also not always available-less than 50% of health systems have access to PST, making this approach less likely to be generalizable [60].…”
Section: Advantages and Disadvantages Of Potential Workflowsmentioning
confidence: 99%
“…Preoperative allergy assessment and/or de-labeling also involve a significant financial and time outlay. Liu et al performed an evaluation of the cost of implementing PST relative to the benefit, and they found that the degree to which performing PST made financial sense was dependent on the rates of C. difficile infection and SSIs at an institution [59]. PST supplies and training are also not always available-less than 50% of health systems have access to PST, making this approach less likely to be generalizable [60].…”
Section: Advantages and Disadvantages Of Potential Workflowsmentioning
confidence: 99%
“…Although penicillin allergy testing, especially skin testing, has proven to be a reliable and cost‐effective intervention in removing an inaccurate penicillin allergy label, 2,30–32 it does not translate to a quick solution. Removing false penicillin allergy labels are a challenge with time constraints, physician knowledge, clinical scenario, and patient preferences intermingling.…”
Section: How To Intervene: a Practical Approachmentioning
confidence: 99%